Inotuzumab Ozogamicin Monotherapy as an Outpatient Salvage Treatment in Relapsed Refractory B-Cell Acute Lymphoblastic Leukemia: Compassionate Access - Radhakrishnan, Vivek S.; Modak, Ketan; Bhave, Saurabh J.; Kumar, Jeevan; Roychowdhury, Mita; Ghosh, Manik; Parihar, Mayur; Arora, Neeraj; Mishra, Deepak K.; Nair, Reena; Chandy, Mammen (Indian Journal of Medical and Paediatric Oncology, 2021)
Relapsed and refractory (RR) acute lymphoblastic leukemia (ALL) poses unique and difficult challenges to a practicing clinician in India where access to novel immunotherapies is limited. Between 2017 and 2020, eight patients with B-cell ALL at our center received inotuzumab ozogamicin (IO) monotherapy on compassionate access, as salvage therapy after at least two lines of conventional therapy failure, and most often as outpatient infusion. Eight patients (21–60 years, three females) received IO. Three patients had morphologic relapse and five patients reported persistent measurable residual disease (MRD). The best response on IO therapy achieved was negative MRD in six of seven patients and complete response (CR) with persistent MRD in one. One patient died (intracranial hemorrhage) before completion of first cycle. All responding patients were transplant eligible and four patients (57%) underwent allogeneic hematopoietic cell transplantation (Allo-HCT). Median follow-up of this cohort is 9 months (4–29.6 months), four patients (57%) are alive as stable with negative MRD. No significant infusion reactions occurred during therapy. Three patients developed grades III and IV neutropenia, two patients showed grade III transaminitis, and two patients developed post-HCT severe sinusoidal obstruction syndrome (SOS). IO is a feasible outpatient based salvage therapy to improve the remission status in RR B-cell ALL.
Keywords: inotuzumab ozogamicin; minimal residual disease; relapsed refractory B-cell ALL; immunotherapy; targeted therapy; hematopoietic cell transplantation